EFEKTIVITAS EKSTRAK ETANOL DAUN KIRINYUH (CHROMOLAENA ODORATA L) SEBAGAI ANTIBAKTERI SALMONELLA TYPHI DAN STAPHYLOCOCCUS AUREUS - Fadia, Fadia; Nurlailah, Nurlailah; Helmiah, Tini Elyn; Lutpiatina, Leka (Jurnal Riset Kefarmasian Indonesia, 2020)
Salmonella typhi and Staphylococcus aureus are pathogenic bacteria that cause infectious diseases. Treatment of these diseases can be done by giving antibacterial drugs. One of the plants that can be used as an antibacterial drug is the leaves of Chromolaena odorata L. due to the presence of chemical compounds such as flavonoids, tannins, and saponins that have the potential as antibacterial. This study aims to determine the Minimum Inhibitory Concentration (MIC), and Minimum Bactericidal Concentration (MBC) ethanol extract of Chromolaena odorata L. leaves on the growth of Salmonella typhi and Staphylococcus aureus. This research is the initial stage of the development of herbal medicines to treat Salmonella typhi and Staphylococcus aureus infections. The study consisted of 5 treatments, namely concentrations of 20%, 40%, 60%, 80%, and 100% ethanol extract of Chromolaena odorata L. leaves with five repetitions. The antibacterial activity test was carried out by MIC and MBC methods. The research material uses leaves from Chromolaena odorata L. in the Sungai Besar area, Banjarbaru, South Kalimantan, Indonesia. The results showed that the average MIC yield of ethanol extract of Chromolaena odorata L. leaves against Salmonella typhi: 20% and Staphylococcus aureus: 20%. While the average yield of MBC values ​​against Salmonella typhi: 40% and Staphylococcus aureus: 40%. Based on the results obtained, it can be concluded that the ethanol extract of Chromolaena odorata L. leaves has an inhibitory effect on the growth of Salmonella typhi and Staphylococcus aureus. Chromolaena odorata L. leaves has potential as herbal medicine against bacterial infections but requires further research to determine its effect in vivo.